The neighbours of Eyjafjallajökull : the phenomenon of social capital - Elísabet I. Þorvaldsdóttir 1972- (2014)
The goal of this research is to examine how the phenomenon social capital can be used to explain and describe the impact of situations on the lives of people during the time of the eruption of the Eyjafjallajokull volcano. The issue is explored through construction and analysis of a number of narratives representative of a farming community that has experienced two separate crises, i.e. the man-made economic crisis of 2008, and non-human natural crisis of the eruption of the Eyjafjallajökull volcano in 2010. The narrative is therefore to explain how the people who were relying on farming and other small business activities managed to survive during the eruption. Furthermore, it explains the effect the eruption had on their lives and why they seem to be optimistic about the future and how they explain the opportunities due to the unforeseen growth in the tourist industry that materialized after the eruption. The investigation brings to the field of study knowledge as to the role of local authorities in the risk assessment processes, how social capital can be a resource to be drawn on when coping with critical situations, and whether local authorities should encourage building up social capital to support the inhabitants of the farming area in its economic development and its preparation for emergencies.